"Nothing, Nothing, Nothing": Dostoevsky and Existentialism - Kujundžić, Dragan (Labyrinth, 2021)
The paper attempts to situate the work of Fyodor Dostoevsky in the tradition of Russian existentialism, and to indicate his influence on the subsequent development of existentialism in its ontological or ethical guise. In fact, Dostoevsky may be seen as the originator of a tradition which will later on influence and be taken up, via Nietzsche and Shestov, by the figures like Emanuel Levinas, Albert Camus or Maurice Blanchot, all explicitly concerned with existentialist questions of debt, guilt or suicide (Kirilov). Dostoevsky's writings are also interpreted in relation to Russian nationalism, and the sense of Russian Messianic election, which at the end of Crime and Punishment coalesce in another destination for Raskolnikov, launching him towards a Messianic future prior to the Abrahamic time and monotheistic sacrificiality. The end of Crime and Punishment imagines another existence for Raskolnikov, before the religious history, or the history tout court, has taken place or time. That time space is akin to something that Jacques Derrida formulated as an advent of an event to-come, a-venir. Dostoevsky is thus, in our interpretation, both a progenitor of the important strains of existentialism, but also a writer returning his hero's existence to an advent of a completely other, time before time, yet to come.